2012
DOI: 10.1111/j.1582-4934.2011.01298.x
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical analysis of myenteric ganglia and interstitial cells of Cajal in ulcerative colitis

Abstract: Ulcerative colitis (UC) is an inflammatory bowel disease with alterations of colonic motility, which influence clinical symptoms. Although morpho-functional abnormalities in the enteric nervous system have been suggested, in UC patients scarce attention has been paid to possible changes in the cells that control colonic motility, including myenteric neurons, glial cells and interstitial cells of Cajal (ICC). This study evaluated the neural-glial components of myenteric ganglia and ICC in the colonic neuromuscu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
85
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(93 citation statements)
references
References 35 publications
(67 reference statements)
6
85
0
1
Order By: Relevance
“…This accumulation is suspected to progressively impair the intestinal function and the quality of life. [8] Active chronic UC can also induce a loss of colonic function [2] and an increased risk of colonic cancer. [9] Our definition of mild CD and UC also excluded the requirement of IM or anti-TNF in the course of the disease because they are usually associated with a worsening of the disease and with an increased incidence of infectious [10][11][12] and oncologic complications.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This accumulation is suspected to progressively impair the intestinal function and the quality of life. [8] Active chronic UC can also induce a loss of colonic function [2] and an increased risk of colonic cancer. [9] Our definition of mild CD and UC also excluded the requirement of IM or anti-TNF in the course of the disease because they are usually associated with a worsening of the disease and with an increased incidence of infectious [10][11][12] and oncologic complications.…”
Section: Discussionmentioning
confidence: 99%
“…[1,2] The aim of CD and UC treatments is not only to induce a corticosteroid-free remission, but also to achieve mucosal healing to change the evolution of the disease. Immunomodulators (IMs) and particularly anti-TNFs are effective to induce mucosal healing in inflammatory bowel diseases (IBD).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, it was found that the damage, loss or function change of ICCs is closely associated with many GI motility disorders after inflammation [5][6][7] . Hence, further studies about the growth, development and maintaining mechanism of the network structure of ICCs in pathologic condition and the cytokines, which regulate the maintenance and survival of ICCs are of great clinical significance [8].…”
Section: Introductionmentioning
confidence: 99%
“…A common finding from studies of the inflamed colon is a reduction in the number of enteric neurons that does not appear to be restricted to specific neural populations. This has been observed in the myenteric plexus of mouse and guinea pig (Boyer et al 2005;Linden et al 2005) and the submucosal plexus of rats (Sanovic et al 1999) with trinitrobenzene sulfonic acid (TNBS)-induced colitis, as well as the myenteric plexus of the human ulcerative colitis (UC) patients (Bernardini et al 2012;Geboes and Collins 1998). Enteric neuron density remains diminished following the resolution of inflammation (Linden et al 2005).…”
Section: Effects Of Colitis On the Ensmentioning
confidence: 99%